Paging more than one page - Feuerstein, E. (1997)
In this paper we extend the Paging Problem to the case in which each request specifies a set of pages that must be present in fast memory to serve it. The interest on this extension is motivated by many applications in which the execution of each task may require the presence of more than one page in fast memory. We introduce three different cost models that can be applied in this framework, namely the Full, Uniform and Constant cost models, and study lower and upper bounds for each one of them, using competitive analysis techniques.